2021
DOI: 10.1108/jfra-09-2020-0266
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on integrated reporting from 2011 to 2020

Abstract: Purpose This study aims to furnish the systematic literature review on integrated reporting (IR) and answer three research questions: How has the IR concept been developed recently across the different countries? How can the literature of IR be allocated among different focus areas/themes? What are the future opportunities available for IR? Design/methodology/approach The methodology involves selection, classification and categorization of 110 articles on IR into their focus areas, journals, time distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 106 publications
0
20
0
Order By: Relevance
“…NFIrequested by law and by various organizations, such as the Organization for Economic Cooperation and Development (OECD), the International Federation of Accountants (IFAC), and the International Finance Corporation (IFC)-has been and is the object of interest for researchers. Recent studies, such as that by Soriya and Rastogi (2021), show the need to continue advancing in this type of study. Research also considers it very important to identify and report business risks accurately, with special attention to risks from technology and cybersecurity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…NFIrequested by law and by various organizations, such as the Organization for Economic Cooperation and Development (OECD), the International Federation of Accountants (IFAC), and the International Finance Corporation (IFC)-has been and is the object of interest for researchers. Recent studies, such as that by Soriya and Rastogi (2021), show the need to continue advancing in this type of study. Research also considers it very important to identify and report business risks accurately, with special attention to risks from technology and cybersecurity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As IR gains momentum in India, it is essential to ascertain its costs and benefits (Islam, 2020). According to Soriya and Rastogi (2021), to determine the feasibility of IR in India, it is necessary to examine its disclosure practices and analyze shareholders' and accountants' perceptions of this new system.…”
Section: Introductionmentioning
confidence: 99%
“…Much as IR is not yet mandatory in most developing countries like Uganda, its practice by organisations is a best practice given the underlying significance. JFRA 21,2 Thirdly, there have been limited studies that empirically examine the determinants of IR in emerging countries in Africa as this has been evidenced in the Soriya and Rastogi (2021) study whereby out of 110 articles reviewed, only 8 articles mentioned African countries. Soriya and Rastogi (2021) found that only 6 articles mentioned South Africa whilst 2 articles mention Uganda and Nigeria.…”
Section: Introductionmentioning
confidence: 99%